Pengaruh Sistem Informasi Akuntansi, Audit Internal, Kualitas Sumber Daya Manusia, Pengawasan Keuangan Daerah Dan Penerapan Standar Akuntansi Pemerintahan Terhadap Kualitas Laporan Keuangan Di Instansi Pemerintah (Studi Kasus Dinas Ketahanan Pangan, Tanaman Pangan Dan Hortikultura Provinsi Lampung) - Kusnadi, -; Luthfi, Muhammad; Nurmilla, Mely (Universitas Malahayati, 2025)
This research was motivated by several weaknesses in the financial reporting of the Lampung Province Food Security, Food Crops, and Horticulture Agency (KPTPH), a government agency that is not yet fully qualified. These weaknesses include: 1) Lack of adequate human resources for preparing financial reports at the work unit and regional levels, 2) Inadequate administration, 3) Inefficient budget utilization due to negligence in implementation, 4) Minimal employee knowledge of government accounting regulations, and 5) A suboptimal internal control system.This research used a quantitative approach, with data collected through questionnaires from all finance employees at the agency. Analysis was conducted using SmartPLS version 4. The results indicate that all variables—Accounting Information Systems, Internal Audit, Human Resource Quality, Regional Financial Supervision, and Implementation of Government Accounting Standards—have a positive and significant impact on financial report quality. The Adjusted R-Square of 0.976 indicates that 97.6% of the variation in the quality of financial reports can be explained by these variables, while the remaining 2.4% is explained by other factors not examined.